Wave phenomena : modern theory and applications - Rogers, C.; Moodie, T. Bryant (Thomas Bryant), 1944- (North-Holland mathematics studies, 1984)
This volume contains 35 of the contributions to the international meeting Wave Phenomena: Modern Theory and Applications, held at the University of Toronto, Canada, at the end of June 1983.